2021
DOI: 10.1016/j.apnr.2021.151418
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of critical care nurses caring for patients with COVID-19 during the 2020 pandemic: A qualitative study

Abstract: Due to a lack of literature about US critical care nurses caring for patients with coronavirus disease 2019 (COVID-19), the aim of this study was to examine their experiences caring for these patients. COVID-19 placed nurses at the forefront of battling this pandemic in the intensive care unit (ICU). Emerging international evidence suggests nurses experience psychological and physical symptoms as a result of caring for these patients. A qualitative descriptive design was used. Using purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
221
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(287 citation statements)
references
References 22 publications
21
221
0
14
Order By: Relevance
“…Discourses routinely co‐exist with one another (Powers, 2013 ). The discourse of ‘nurse‐as‐hero’ during COVID‐19 has been discussed by other authors (Brophy et al, 2021 ; Cox, 2020 ; Einboden, 2020 ; J. M. Gordon et al, 2021 ; Mohammed et al, 2021 ). Mohammed et al ( 2021 ) concluded that the nurse‐as‐hero discourse was positioned as a reward for nurses and as a convenient means to ignore the lack of support that nurses receive from their places of work, managers and the government.…”
Section: Discussionmentioning
confidence: 97%
“…Discourses routinely co‐exist with one another (Powers, 2013 ). The discourse of ‘nurse‐as‐hero’ during COVID‐19 has been discussed by other authors (Brophy et al, 2021 ; Cox, 2020 ; Einboden, 2020 ; J. M. Gordon et al, 2021 ; Mohammed et al, 2021 ). Mohammed et al ( 2021 ) concluded that the nurse‐as‐hero discourse was positioned as a reward for nurses and as a convenient means to ignore the lack of support that nurses receive from their places of work, managers and the government.…”
Section: Discussionmentioning
confidence: 97%
“…The COVID-19 pandemic will most likely have a tremendous influence on ICU nurses' mental health and potentially their continuation in the workforce. Although the experiences of nurses in other countries, [12][13][14][15][16] nurse managers, 17 nurses from 1 ICU, 18 and HCWs in general [19][20][21] have been reported, at the initiation of this survey, we found no published studies that described the national ICU nurse experience in the United States. To fully support ICU nurses currently and after the pandemic, it is of critical importance that we explore nurses' perspectives about working in ICUs during this time.…”
mentioning
confidence: 78%
“…The copyright holder for this preprint this version posted October 29, 2021. ; https://doi.org/10.1101/2021.10.28.21265608 doi: medRxiv preprint who came in contact with health professionals were mainly feelings of rejection, fear, and categorisation (Duan et al, 2020). Recent research, which is extremely limited on this issue due to the fact that this outbreak is quite recent, has started to record the experience of health professionals during the pandemic, although there is no similar research in Greece and Cyprus (Eftekhar et al, 2020;Gordon et al, 2021;Montgomery et al, 2021;Smyrnakis et al, 2021). It is characteristic that such opinions were expressed in the daily press during the pandemic period about health professionals that were forced to separate from their families and live in hotels, thus preventing further spread of the virus.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%